PENGARUH KETERIKATAN KERJA, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. MNC Wahana Wisata - Achmad Jajang Rukanda; Ahmad Faisal (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2023)
research was conducted at PT.MNC Wahana Wisata, Jakarta. MNC group is a multinational company in Indonesia. This study population of employees of PT.MNC Wahana Wisata. Amounting to 70 people which is a saturated sample. The study aims to determine whether there is an effect between the factor or dimension of work engagement, organization culture, and job satisfaction on work performance. Associative research method with conducted with a quantitative approach to research survey techniques, and descriptive research with causality variables. The result should that partially three exogenous variables are work engagement, organization culture, and job satisfaction, have a significant effect on the endogenous variable is work performance. Suggestions submitted to the management company, should pay attention and increase the intensity of the factors of work engagement, organization culture, and job satisfaction to achieve high work performance to improve the company high work performance to create added value and make it even better.Keywords: work engagement, organization culture, job satisfaction, work performance